2019
DOI: 10.3892/ijmm.2019.4397
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of HDAC2 by sodium butyrate alleviates apoptosis of kidney cells in db/db mice and HG‑induced NRK‑52E cells

Abstract: Butyrate is short-chain fatty acid, which is produced by intestinal microbiota metabolizing dietary fibers. Butyrate participates in various physiological processes predominantly by activating G-coupled-receptors, inhibiting histone deacetylases (HDACs) and serving as an energy substrate. Previous studies have shown that butyrate plays a protective role in diabetic nephropathy (DN); however, the exact mechanism remains unclear. The present study identified that providing sodium butyrate (NaBu) by gavage reliev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…Butyrate is one of short chain fatty acids (SCFAs) produced by intestinal bacteria in gut which ferment food fiber. As an endogenic histone deacetylase (HDAC) inhibitor, butyrate remodels the acetylating state on histone and thus gene expression profile [ 12 , 13 ]. It was also reported that butyrate increases the activity of histone acetyltransferases (HAT) and promotes the destined gene transcription [ 12 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Butyrate is one of short chain fatty acids (SCFAs) produced by intestinal bacteria in gut which ferment food fiber. As an endogenic histone deacetylase (HDAC) inhibitor, butyrate remodels the acetylating state on histone and thus gene expression profile [ 12 , 13 ]. It was also reported that butyrate increases the activity of histone acetyltransferases (HAT) and promotes the destined gene transcription [ 12 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In light of its profound effect on gene expression, butyrate affects various cellular events, including proliferation, cell cycle, apoptosis, differentiation, migration, and invasiveness [ 12 , 16 19 ]. Butyrate was confirmed to be an effective small molecule in inhibition of diabetes and various tumors [ 13 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Administration of sodium butyrate (NaBu), the major members of SCFAs, ameliorates mesangial matrix expansion, brosis and in ammation in the kidneys of STZ-induced diabetic rats [30,31]. In vitro study, NaBu acted as an antioxidant in HG-induced NRK-52E cells and suppressed HG-induced apoptosis of NRK-52E cells through inhibiting HDAC2 [32]. In vivo study, dietary ber protects against DKD through modulation of the gut microbiota, enrichment of SCFA-producing bacteria, and increased SCFA production, so that it reduced expression of genes encoding in ammatory cytokines, chemokines, and brosis-promoting proteins in diabetic kidneys via GPR43 and GPR109A [33].Recent studies found GPR41 and GPR43 protein expressed in the distal renal tubules and collecting tubules, and found SCFAs lowered TNF-α induced MCP-1 expression by reducing phosphorylation of p38 and JNK in a GPR41/43-dependent manner in human renal cortical epithelial cells(HRCEs) [34].…”
Section: Discussionmentioning
confidence: 99%
“…SCFAs can be used by the host for the biosynthesis of lipids, cholesterol, and proteins or as an energy source by gut mucosal cells (18). The effects of SCFAs are in part mediated by G-protein coupled receptors (GPR41, GPR43, and GPR109A) and histone deacetylase (HDAC), which are related to oxidative stress, immune, and inflammatory responses (19)(20)(21)(22).…”
Section: Short-chain Fatty Acidsmentioning
confidence: 99%